Cross-sectional study of drug utilisation in a Chinese neonatal unit. Issue 5 (May 2020) - Yue, Yan; Chen, Libin; Choonara, Imti; Xiong, Tao; Ojha, Shalini; Tang, Jun; Wang, Yan; Zeng, Linan; Shi, Jing; Wang, Hua; Mu, Dezhi
Objective: This study aimed to describe drug utilisation in a large Chinese neonatal unit and to compare the findings with those from other countries. Methods: Data were collected from electronic medical records. Prescription drugs were defined as the number of unique medication names for each patient. Medicine doses were defined as the total number of doses of all medicines administered. Information was collected regarding drugs prescribed to inpatients between March 1 and April 1 2018 in the neonatal intensive care unit and the general neonatal ward of West China Second University Hospital. Results: The 319 neonates received 1276 prescription drugs and 11, 410 medicine doses involving 81 drugs. Vitamin K1, hepatitis B vaccine, and cefoperazone-sulbactam were the three most frequently prescribed drugs. Antimicrobials were the most frequently used group of medicines, with cefoperazone-sulbactam and piperacillin-tazobactam the most frequently used in an off-label manner. Domperidone and simethicone were both widely used. Conclusions: The most commonly prescribed antimicrobials differed greatly from those reported for other countries. The evidence base for the use of some medicines is poor, and is indicative of irrational prescribing.